The strategies applied by teachers in teaching speaking - Maryanti Maryanti; Sofyan Abdul Gani; Saiful Marhaban (Universitas Syiah Kuala, 2021)
The teaching of English is very important for young learners in the era of industry 4.0. A successful teacher is largely determined by the strategies he/she uses in the learning process. The students in SMP Negeri 1 Sabang were very interested in speaking English. They had won many events in English speaking competitions and mostly reached a good score on speaking test. This research was conducted to find out the strategies used, problems, and the solutions faced by the teachers during a teaching process at SMP Negeri 1 Kota Sabang. The research method of this study is descriptive qualitative by employing observation and interview guide sheets as the research instruments. The participants of this research were three English teachers at SMP Negeri 1 Sabang. The results show that the teachers used various kinds of strategies in teaching speaking; role-play, picture describing, interview, and simulations. It was also found that there were five obstacles during the teaching process; some students disturb their friends, ignore the learning process, bully their friends, lack in vocabulary, and possess limited teaching and learning duration. The solutions in solving the problems show that the teachers use four approaches to solve the problems: teachers maximized student's centered, motivated deeply and sustainably, provided a new vocabulary, and extra time online. It is suggested that English teachers should always find new ideas, strategies, or techniques in teaching-learning so that students are interested in taking part actively in the learning process.